Exploring environmental factors contributing to Parkinson’s disease in AfrAbian populations - Wael Mohamed (Academia Biology)
Parkinson’s disease (PD) is a global disease. However, there is a lack of research specifically focused on the AfrAbian population. Climate change, driven mainly by global warming, is linked to detrimental health impacts, including an increased frequency and intensity of heat waves. Neurological diseases, including neurodegenerative syndromes like Alzheimer’s disease, Parkinson’s disease, and motor neuron illnesses, have been increasingly seen and recorded in the scientific literature. Although there is much research demonstrating the growth of neurodegenerative disorders, the relationship between environmental variables such as global warming, air pollution, heavy metals, and pesticides and the higher occurrence of these illnesses is still unknown. The current article primarily aims to examine the relationship between climatic changes, air pollution, pesticides, and heavy metals and the occurrence of PD. Initially, we evaluate the influence of exposure to these variables on the cause or origin of Parkinson’s disease. In addition, we will investigate how these variables disrupt processes such as excitotoxicity, oxidative stress, and neuroinflammation, all of which are strongly linked to Parkinson’s disease (PD). This study presents a plausible rationale for the adverse effects of environmental influences on the brain, which are pivotal in the progression or onset of Parkinson’s disease from an AfrAbian standpoint.